The Marshall plan for libraries. American books at the University of Florence from the postwar period to the Sixties - Grifoni, Giovanna (JLIS.it, 2021)
The subject of the contribution is the postwar donations of American books to the University of Florence, the CARE Mission, the role of the US Information Service (USIS) in the promotion and spread of American culture in Italy, and lastly the origin of the North American Library in Florence. Particular emphasis is given to the commitment of Italian intellectuals, who were refugees in the US, in the growth of the library collections of the University of Florence and to the active collaboration between Piero Calamandrei, Chancellor of the University and President of the Tuscan Section of the Italian-American Association, and Gaetano Salvemini, still teaching in the United States. The cultural aid plan also mentions the American Libraries founded in Italy by USIS, and particularly the Florentine headquarters of Palazzo Feroni, whose patrimony was given in the mid-sixties to the Institute of American Studies of the Faculty of Magisterium to set up the North American Library.